2021
DOI: 10.3389/fimmu.2020.602823
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T Lymphocytes: Crucial Players in Sjögren’s Syndrome

Abstract: Primary Sjögren’s syndrome (pSS) is a chronic autoimmune disease associated with damage to multiple organs and glands. The most common clinical manifestations are dry eyes, dry mouth, and enlarged salivary glands. Currently, CD4+ T lymphocytes are considered to be key factors in the immunopathogenesis of pSS, but various studies have shown that CD8+ T lymphocytes contribute to acinar injury in the exocrine glands. Therefore, in this review, we discussed the classification and features of CD8+ T lymphocytes, sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 136 publications
1
33
0
Order By: Relevance
“…Therefore, it is possible that the patients in the early stage with less lymphocytic infiltration have a different overview of immunopathogenesis. Although several studies reported the pathogenetic roles of CD8+ T cells, the involvement of CD8+ T cells in disease initiation remains to be further explored 56 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that the patients in the early stage with less lymphocytic infiltration have a different overview of immunopathogenesis. Although several studies reported the pathogenetic roles of CD8+ T cells, the involvement of CD8+ T cells in disease initiation remains to be further explored 56 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Tfhs can promote secretion of proinflammatory cytokines in target tissues, such as IL-17 and IFN, participating in the specific pathological functions of different stages of SS development ( 24 , 25 ). Various studies have shown that CD8 + T lymphocytes also contribute to damage to exocrine acini ( 26 ). On the other hand, a large number of B cells proliferate and become activated in the salivary glands.…”
Section: Histopathological Features Of Salivary Glandsmentioning
confidence: 99%
“…SS glandular lesions are due to massive infiltration of inflammatory cells (including T and B lymphocytes, natural killer cells, dendritic cells, and macrophages) and the formation of ectopic germinal centers (8)(9)(10)(11). So far, SS etiology involves poorly elucidated genetic factors.…”
Section: Introductionmentioning
confidence: 99%